Electrically Tunable Goos–Hänchen Effect with Graphene in the Terahertz Regime. Issue 11 (14th July 2016) - Fan, Yuancheng; Shen, Nian‐Hai; Zhang, Fuli; Wei, Zeyong; Li, Hongqiang; Zhao, Qian; Fu, Quanhong; Zhang, Peng; Koschny, Thomas; Soukoulis, Costas M.
Abstract : Goos–Hänchen (G–H) effect is of great interest in the manipulation of optical beams. However, it is still fairly challenging to attain efficient controls of the G–H shift for diverse applications. Here, a mechanism to realize tunable G–H shift in the terahertz regime with electrically controllable graphene is proposed. Taking monolayer graphene covered epsilon‐near‐zero metamaterial as a planar model system, it is found that the G–H shifts for the orthogonal s‐polarized and p‐polarized terahertz beams at oblique incidence are positive and negative, respectively. The G–H shift can be modified substantially by electrically controlling the Fermi energy of the monolayer graphene. Reversely, the Fermi energy dependent G–H effect can also be used as a strategy for measuring the doping level of graphene. In addition, the G–H shifts of the system are of strong frequency‐dependence at oblique angles of incidence, therefore the proposed graphene hybrid system can potentially be used for the generation of terahertz "rainbow, " a flat analog of the dispersive prism in optics. The proposed scheme of hybrid system involving graphene for dynamic control of G–H shift will have potential applications in the manipulation of terahertz waves. Abstract : A monolayer graphene is investigated in a hybrid system with metamaterial for achieving an electrically controllable Goos–Hänchen effect in the terahertz regime. It is found that the Goos–Hänchen shift can be substantially modified by changing the doping level of graphene. In addition, the frequency and polarization dependent responses also suggest efficient manipulation on terahertz beams.